Ginásio Estadual ""Martinm Afonso"": uma reconstrução histórica de imagens (1931-1971) - Beatove, Rosa Maria Del Salvador (2014)
This Master's thesis is about the first public school to offer secondary education in São Vicente, the Ginásio Estadual ""Martim Afonso"" through images. It shows particular attention to the use of school's uniforms in the pedagogical practices of the institution. The investigation extended from the first year of that institution, in 1931, until 1971, when, by law 5692/71, the ""ginásio escolares"" have extinguished, being replaced by first and second grade´s schools. Aims to understand the early years of the institution, particularly about the school´s uniform in the light of reflection António Nóvoa (1999) in the form of educational organization.